Pemberdayaan Ekonomi Masyarakat Pesisir Pantai Sadeng Gunungkidul melalui Pengolahan Ikan Tuna - Ernoiz Antriyandarti; Umi Barokah; Raden Baskara Katri Anandito; Wiwit Rahayu; Adisti Regita Ramadani; Alifa Putri Madina (Warta LPM, 2023)
The coast of Sadeng Beach is a large potential for marine and fishery resources, which is, one of the potentials is tuna fish commodities. However, the utilization of these resources is still not optimal. The limited use of technology has hampered the processing and marketing of the products, resulting in a decrease in the economic value of tuna products. This Program Kemitraan Masyarakat (PKM) activity aims to boost community development by empowering the processing of marine fish products. So that, they become products that are worth selling higher. Empowerment carried out includes the provision of materials, equipment, and training in the manufacture of processed tuna products aimed at self-reliance and community self-reliance. The training covers how to process tuna raw materials from start to finish which includes raw material preparation, storage, additional seasoning, packaging, and distribution. The activity was carried out in Pucung Village, Girisubo District, Gunungkidul Regency by involving members of the Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) Harapan. The method used in this activity is the Participatory Rural Appraisal (PRA) method which involves active community participation and empowerment. Activities include providing materials and practices for processing tuna fish into tuna cracker products, tuna nuggets, and tuna tofu. The program impacts increasing knowledge and skills of tuna fish processing for empowering partners. Through this activity, the women of the UPPKS Harapan group can contribute economically to the household. The training activities were held on June 11 2022 for the assistance stage for the introduction of tuna processing materials, June 12-October 2022 for product marketing assistance, November 2 2022 assistance for creating social media content until the final evaluation stage is ongoing.